2004
DOI: 10.1017/s0305000904006488
|View full text |Cite
|
Sign up to set email alerts
|

Expressing communicative intents in Estonian, Finnish, and Swedish mother–adolescent interactions

Abstract: A B S T R A C TThe present article focused on two types of communicative intent (directing behaviour vs. eliciting talk) expressed by mothers and teenagers during everyday family interactions in Estonian, Finnish, and Swedish mono-and bicultural families. Three monocultural groups consisted of 17 Estonian, 19 Swedish, and 18 Finnish families living in their country of origin ; two bicultural and bilingual groups consisted of 18 Estonian and 18 Finnish families residing in Sweden. All the children were between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
(70 reference statements)
2
23
0
Order By: Relevance
“…As these words are used to refer to daily games and routines, people who are participating in the child's daily activities and sound effects, these are likely to be used often and during the times when the child pays attention to the object or activity. High use of directives is also correlated with talking less and expecting less verbalization from children (Tulviste et al, 2004). Our findings also support the noun bias in early vocabulary, in both comprehension and production, found in several other languages (Bornstein et al, 2004a ;Caselli et al, 1995 ;Fenson et al, 1994;Gentner, 1982 ;Nelson, 1973 ;Stolt et al, 2008 ;Wehberg et al, 2007).…”
Section: Proportions Of Words From Different Categoriessupporting
confidence: 86%
See 2 more Smart Citations
“…As these words are used to refer to daily games and routines, people who are participating in the child's daily activities and sound effects, these are likely to be used often and during the times when the child pays attention to the object or activity. High use of directives is also correlated with talking less and expecting less verbalization from children (Tulviste et al, 2004). Our findings also support the noun bias in early vocabulary, in both comprehension and production, found in several other languages (Bornstein et al, 2004a ;Caselli et al, 1995 ;Fenson et al, 1994;Gentner, 1982 ;Nelson, 1973 ;Stolt et al, 2008 ;Wehberg et al, 2007).…”
Section: Proportions Of Words From Different Categoriessupporting
confidence: 86%
“…Tardif, 1996). Comparative studies of mother -child interaction have found that the speech directed towards Estonian children is more directive than the speech of American English, Finnish and Swedish mothers (Junefelt & Tulviste, 1997 ;Tulviste, Mizera & De Geer, 2004). For instance, it has been found that North American mothers' speech contains a high proportion of nouns whereas Asian mothers' speech contains proportionally more verbs (see Hoff, 2006).…”
Section: Word Comprehension and Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Euro-American mothers have been found to praise their children more often than Estonian and Swedish mothers whereas Estonian mothers have been found to use more regulation than Euro-American and Swedish mothers (Junefelt and Tulviste, 1997). Estonian mothers have, however, been found to use a highly directive conversational style with a high proportion of imperatives (Tulviste, 2004a;Tulviste et al, 2004) compared to Finnish, Swedish, and Latvian mothers. Estonian mothers have, however, been found to use a highly directive conversational style with a high proportion of imperatives (Tulviste, 2004a;Tulviste et al, 2004) compared to Finnish, Swedish, and Latvian mothers.…”
Section: Cross-cultural and Quasi-experimental Studiesmentioning
confidence: 94%
“…Tulviste (2000) observed the same pattern of maternal language when comparing Estonian and Euro-American motherϪadolescent mealtime interactions. Similarly, in a comparative study of mothers' interaction with early adolescents in Estonian and Swedish mono-and bicultural families (De Geer and Tulviste 2002;Tulviste, Mizera and De Geer 2004), the Estonian mothers differed from Finnish and Swedish mothers in the high frequency of using behavioural directives, and in their preference for imperatives. In addition, the Estonian mothers talked as little as the stereotypically taciturn Finns, but were proportionately most active in encouraging talking (Tulviste et al 2004).…”
Section: Talkativeness In Finland Estonia and Swedenmentioning
confidence: 98%